(untitled) (Quest Journal of Management and Social Sciences, 2025)
Background: Financial literacy plays a crucial role in how individuals make investment decisions, guiding them in managing risk, achieving returns, and pursuing long-term financial goals. In a rapidly evolving financial environment, limited financial knowledge can lead to poor decisions, while higher literacy enhances rational investment behavior and financial well-being. Purpose: This research investigates financial literacy, investment decisions, and challenges faced by Nepalese families in Kathmandu Valley. Recognizing the crucial role of financial literacy in sound decision-making. The study examines the socio-demographic characteristics and challenges that influence investment choices. The objective of this study is to analyze the role of financial literacy in investment decisions. Design/methodology/approach: Explanatory research design is used in this study. A total of 408 urban Nepalese families from the Kathmandu Valley were selected as a sample using the convenience sampling method. The Theory of Planned Behavior is used. To examine the data, both descriptive and inferential statistics were used. SEM was used to analyze the data. Findings: According to this study, market volatility, lack of financial knowledge, emotional biases, and the difficulty in finding suitable investment opportunities are the major challenges faced when making investment decisions. Respondents recommend managerial remedies, including online resources and workshops on financial awareness. Investment decisions are significantly impacted by financial behavior, knowledge, skills, and money management, as confirmed by the structural model. Conclusion: The study concludes that financial behavior, knowledge, skills, and money management have a significant impact on investment decisions, while financial attitude has no direct impact on investment decisions. The results provide complex insights into how urban Nepalese families make financial decisions. Keywords: Theory of Planned Behavior, Financial Literacy, Investment Decision, Kathmandu Valley, Structural Equation Modeling